2022
DOI: 10.3991/ijoe.v18i14.35077
|View full text |Cite
|
Sign up to set email alerts
|

Open Research Tools for the Learning Technologies Innovation Lab

Abstract: Orchestrating scientific work in educational research laboratories is demanding, especially when many interdisciplinary perspectives are involved. A monolithic approach does not suffice here. This paper describes an open-source architecture for an educational research laboratory. The presented system assists interdisciplinary scientists in implementing prototypes, evaluating new didactical approaches, researching collaborative learning processes, collecting learning analytics data, abstracting and automating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It can be concluded that self-regulated statistics learning requires advanced scaffolds as it has greater complexity and abstraction to support students in achieving maximum performances. This evidence indicates that university student education should promote self-regulated learning skills, either integrated or as a standalone subject [31], [32], [33], [34], [35]. Scaffolds for the more abstract subject could be enhanced respecting their characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…It can be concluded that self-regulated statistics learning requires advanced scaffolds as it has greater complexity and abstraction to support students in achieving maximum performances. This evidence indicates that university student education should promote self-regulated learning skills, either integrated or as a standalone subject [31], [32], [33], [34], [35]. Scaffolds for the more abstract subject could be enhanced respecting their characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…As identified in [40], 'orchestrating scientific work in educational research laboratories is demanding, especially when many interdisciplinary perspectives are involved'. This applies to the case of innovation ecosystems in medicine at large as well as in any specific case of tackling a disease or a pathology.…”
Section: Discussionmentioning
confidence: 99%
“…the creation of collaborative spaces [5] and unplugged areas [13] where interaction and creativity can occur including the use of games to teach learning concepts [35]. The availability of Open-source architecture for educational research laboratories for concurrent experiments, connected clients, and other use cases like VR and smart environments may also be employed [40]. The days of library walls covered in signs indicating quiet areas and reading areas are long gone.…”
Section: Data Gathered From Research Gaps and Research Recommendationsmentioning
confidence: 99%